ANALISIS SISTEM PENGADAAN, PENGEMBANGAN DAN PENGENDALIAN INTERN SISTEM INFORMASI AKUNTANSI PADA PT. BANK SULSELBAR CABANG BULUKUMBA - Fitriani, Fitriani; Asirah, Andi (Universitas Patria Artha, 2023)
The purpose of this study was to determine the Analysis Of The Procurement System,Development And Internal Control Of The Accounting Information System At PT. BankSulselbar Cabang Bulukumba. So that this research will provide results about howthe Sulselbar bank is doing to get the accounting information system, and how the development of the system it has used, and how to control the information bneeded, and have the right and relevant value.In this study using a qualitative approach. Where researchers directly observe. The object under study which will then describe, describe and explain the procuremen, development, and internal control of the accounting information system at Pt.Bank Sulselbar bulukumba branch. Furthermore, the data collection methods used are documentation, interviews, and library reviews.The results show that the system for procurement, development and internal control ofaccounting information systems at PT. Bank Sulselbar Cabang Bulukumba Branch, is still fully implemented at the head off office. Information systems are obtained by renting a system from a system developer which is then developed using the SLDC (System Development life Cycle) method.